Associated Gas Monetization via miniGTL : Conversion of Flared Gas into Liquid Fuels and Chemicals - Fleisch, Theo (World Bank, Washington, DC, 2015)
The large scale conversion of natural gas to liquid fuels (GTL) and chemicals (GTC), collectively called ‘miniGTL’ for convenience in this report - has been practiced for decades. For instance, a world scale GTL plant can convert 300 MMscfd of gas into 30,000bpd of diesel or gasoline while a world scale methanol plant produces about 2500tpd of methanol from about 75 MMscfd of gas. Over the last few years, miniGTL technologies have been developed to monetize smaller volumes of gas (less than 25 MMscfd) and thereby offer opportunities to extinguish flares. The engineering of such plants focuses on modular design, simplicity, automation and robustness of operation. In our first study reported in February 2012, a small number of companies with commercially viable options were identified, while others needed more time for RD to demonstrate their technologies. Now, two years later, Oberon Fuels, Velocys and CompactGTL are on the brink of multiple commercial plants. The progress of all companies reviewed in our first report will be discussed. This report contains the most comprehensive study of miniGTL technologies available today. Over 24 companies have been reviewed and are described in some detail. The goal of this study is the identification of companies that provide relatively low risk, commercially viable options today in order to simplify evaluation and choice for GGFR members in eliminating flares.